Study on the mechanism of efficient extracellular expression of toxic streptomyces phospholipase D in Brevibacillus choshinensis under Mg2+ stress - Shaofeng Chen; Weide Xiong; Xurui Zhao; Weiyi Luo; Xuhui Yan; Yinghua Lu; Cuixue Chen; Xueping Ling (Microbial Cell Factories, 2022)
Abstract Background Phospholipase D (PLD) has significant advantages in the food and medicine industries due to its unique transphosphatidylation. However, the high heterologous expression of PLD is limited by its cytotoxicity. The present study sought to develop an efficient and extracellular expression system of PLD in the non-pathogenic Brevibacillus choshinensis (B. choshinensis). Results The extracellular PLD was effectively expressed by the strong promoter (P2) under Mg2+ stress, with the highest activity of 10 U/mL. The inductively coupled plasma–mass spectrometry (ICP-MS) results elucidated that the over-expression of PLD by P2 promoter without Mg2+ stress induced the ionic homeostasis perturbation caused by the highly enhanced Ca2+ influx, leading to cell injury or death. Under Mg2+ stress, Ca2+ influx was significantly inhibited, and the strengths of P2 promoter and HWP gene expression were weakened. The study results revealed that the mechanism of Mg2+ induced cell growth protection and PLD expression might be related to the lowered strength of PLD expression by P2 promoter repression to meet with the secretion efficiency of B. choshinensis, and the redistribution of intracellular ions accompanied by decreased Ca2+ influx. Conclusions The PLD production was highly improved under Mg2+ stress. By ICP-MS and qPCR analysis combined with other results, the mechanism of the efficient extracellular PLD expression under Mg2+ stress was demonstrated. The relatively low-speed PLD expression during cell growth alleviated cell growth inhibition and profoundly improved PLD production. These results provided a potential approach for the large-scale production of extracellular PLD and novel insights into PLD function.